2019
DOI: 10.1155/2019/2584859
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Long-Term Follow-Up of Pulmonary Diffusion Capacity Reduction Caused by Dose-Dense Chemotherapy in Patients with Breast Cancer

Abstract: Background Our previous study of pulmonary function in 34 patients with early breast cancer without preexisting lung disease showed that anthracycline- and taxane-based adjuvant dose-dense chemotherapy (DDC) caused a significant 16.4% mean reduction in carbon monoxide diffusing capacity (DLCO). The present study reports the pulmonary and oncological outcomes of these patients on long-term follow-up. Patients and methods The primary endpoint was DLCO measured by the pulmonary function test (PFT) performed at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(41 reference statements)
1
2
0
Order By: Relevance
“…The latter was reduced, in particular, in subjects who had received intravenous high-dose courses of chemotherapy for malignant blood disorders prior to allo-HSCT. This finding is in line with reports from various other studies indicating that DL CO is the most sensitive test for detecting chemotherapy-induced lung injury [30][31][32][33][34][35]. In previous studies, we have found impaired gas diffusing capacity in long-term lymphoma survivors after high-dose therapy with autologous stem cell transplantation [33] and in very long-term adult survivors of childhood acute lymphoblastic leukemia [34].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The latter was reduced, in particular, in subjects who had received intravenous high-dose courses of chemotherapy for malignant blood disorders prior to allo-HSCT. This finding is in line with reports from various other studies indicating that DL CO is the most sensitive test for detecting chemotherapy-induced lung injury [30][31][32][33][34][35]. In previous studies, we have found impaired gas diffusing capacity in long-term lymphoma survivors after high-dose therapy with autologous stem cell transplantation [33] and in very long-term adult survivors of childhood acute lymphoblastic leukemia [34].…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies, we have found impaired gas diffusing capacity in long-term lymphoma survivors after high-dose therapy with autologous stem cell transplantation [33] and in very long-term adult survivors of childhood acute lymphoblastic leukemia [34]. Late adverse effects of chemotherapy on gas diffusing capacity have also been shown in patients treated for lung cancer [32] and breast cancer [35]. Although the underlying mechanisms of cytotoxic lung injury are multifactorial and remain unclear, it is thought that microvascular damage may be a common denominator and an important feature [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, DLCO was thought to have the highest radiosensitivity; additionally, to the best of our knowledge, significant lung dose-volume relationships after SRT with ΔDLCO and ΔDLCO/VA have not been previously reported. Although there were conflicting results for DLCO after SRT, it may be difficult to measure ΔDLCO in a retrospective design because DLCO is a vulnerable parameter and can be affected by chemotherapy agents [31,32]. Stephans et al reported correlations of lung ΔFEV1% predicted with lung V5 Gy (cc) and V10 Gy (cc), but there was no correlation between ΔDLCO and lung dose-volume parameters in SRT [33].…”
Section: Plos Onementioning
confidence: 99%